Penerapan Hukum Waris pada Masyarakat Kota Kendari (Studi Banding Hukum Adat, Islam, dan Perdata barat) - Kamaruddin Kamaruddin (Institut Agama Islam Negeri (IAIN) Kendari, 2008)
This research was conducted in Kendari City, Southeast Sulawesi Province.The purpose of this study is (1) To know and analyze the level of understanding of community law of Kendari city especially the application of the customary law of inheritance, Islam or Western Civil. (2) To find out and analyze the tendencies of Kendari City community to the application of the customary law of adat, Islam and Western Civilization.Data collection from population 200 people doing the application of the customary law of adat, Islam or Western Civilization, using random sampling technique (simple random) then collecting using interview and questionnaire method with frequency analysis method to the respondent.The results showed that the level of understanding of community law Kendari is still very low, both understanding the inheritance law of Adat, Islam, and Western civil law. Then the tendency of the Kendari City community to the application of customary, Muslim, and Western civil waris law is more likely to choose Islamic inheritance law because it is considered as a guidance and religious instruction is believed to give benefit and justice rather than customary law or western civil inheritance law.